STRATEGI PENGEMBANGAN BISNIS PRODUK MELALUI PROMOSI MEDIA SOSIAL PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI PONDOK PESANTREN PENDAWA - Sujadi, Didi; Nofryanti; A.Asrorudin (Tensile : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to find out how to use social media and analyze and contribute ideas regarding product business development strategies through social media promotion in micro, small and medium enterprises (MSMEs). Through this community service, business owners can further develop and increase the visibility of their company in the community through effective social media promotions, resulting in maximizing sales or profits. As a result, business owners immediately opened and marketed their companies through e-commerce or online stores and created interesting content on social media. And business people can also expand the range of goods offered by offering a variety of menu choices in the hope of arousing customers' interest in making purchases. Finally, business owners maximize and continue to innovate in their business by expanding their marketing reach and offering wider products and services. Keywords : Business strategy, and promotion.